1956
DOI: 10.1039/jr9560003771
|View full text |Cite
|
Sign up to set email alerts
|

734. Chemical action of ionising radiations in solutions. Part XVI. Formation of labile phosphate esters from purine and pyrimidine ribonucleotides by irradiation with X-rays in aqueous solution

Abstract: Irradiation of purine and pyrimidine ribonucleotides in aqueous solution with X-rays (200 kv) results in the formation of intermediate labile phosphate esters which lead to a post-irradiation release of inorganic phosphate. This release of phosphate, which occurs after irradiation in the presence or absence of oxygen, follows a first-order rate law and is strongly base-catalysed. It is suggested that the radiation-induced lability of the nucleotides is due to the formation of activating carbonyl groups in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1960
1960
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Raleigh et al (1973) reported that the release of inorganic phosphates by y-radiation from AMP at neutral pH was 2-4 times higher in the 3' isomer than in the 5' isomer . A similar preference was noted earlier in the Xirradiation experiments by Daniels et al (1956) . With dApdA preferential cleavage of the 3' end of the internucleotide bond, producing more 5'-dAMP than 3'-dAMP, has been reported (Raleigh et al .…”
Section: Compilation Of the Results Of Radiation-induced Dissociatisupporting
confidence: 76%
“…Raleigh et al (1973) reported that the release of inorganic phosphates by y-radiation from AMP at neutral pH was 2-4 times higher in the 3' isomer than in the 5' isomer . A similar preference was noted earlier in the Xirradiation experiments by Daniels et al (1956) . With dApdA preferential cleavage of the 3' end of the internucleotide bond, producing more 5'-dAMP than 3'-dAMP, has been reported (Raleigh et al .…”
Section: Compilation Of the Results Of Radiation-induced Dissociatisupporting
confidence: 76%
“…3), it can be estimated that only about 40% of the total phosphomonoester groups formed are 5' -phosphomono esters. One cannot rule out whether all the other phosphomonoesters are 3'-phos phomonoesters, since Daniels et al (24) showed that radical attack on the C atom of the sugar moiety results in the formation of a labile phosphate group with the eventual release of inorganic phosphate. Therefore, additional studies, perhaps employing a specific 3' -phosphomonoesterase will be necessary to identify the nature of the 3'-termini.…”
Section: Discussionmentioning
confidence: 99%